Image and screen (Australia : Australian Film and Television School Open Program [production company] ; Hong Kong : Educational Film Services [distributor], 1979)
Describe on quality of image in motion picture cameras
Narrator: Peter Thompson
Keywords: Motion pictures and language; Motion picture cameras